On-orbit operations optimization : modeling and algorithms - Yang, Leping (SpringerBriefs in Optimization,, 2014)
On-orbit operations optimization among multiple cooperative or noncooperative spacecraft, which is often challenged by tight constraints and shifting parameters, has grown to be a hot issue in recent years. The authors of this book summarize related optimization problems into four planning categories: spacecraft multi-mission planning, far-range orbital maneuver planning, proximity relative motion planning and multi-spacecraft coordinated planning. The authors then formulate models, introduce optimization methods, and investigate simulation cases that address problems in these four categories. This text will serve as a quick reference for engineers, graduate students, postgraduates in the fields of optimization research and on-orbit operation mission planning.